Eosinophilic annular erythema is a peculiar subtype in the spectrum of Wells syndrome: a multicentre long‐term follow‐up study. (25th June 2012) - El‐Khalawany, M.; Al‐Mutairi, N.; Sultan, M.; Shaaban, D.
Abstract: Background/Objective Eosinophilic annular erythema (EAE) was proposed to describe annular skin lesions associated with tissue eosinophilia, however, its relation to Well's syndrome (WS) remains a source of controversy. We studied a series of patients to increase awareness of this entity and to clarify its relation to WS. Methods A multicentre study in which the clinical records, histological findings, laboratory results, therapeutic responses and follow‐up of 10 patients were demonstrated. Results The study included seven women and three men with age ranging from 31 to 54 years. The duration of the disease ranged from 3 to 28 months. All patients showed involvement of trunk and extremities. Early lesions were manifested as erythematous plaques, which progressed to well‐developed figurate lesions and ended as large annular lesions with pigmented centre and elevated border. Flame figures were only observed in well‐developed and long‐standing lesions. Blood eosinophilia was found in all patients with different grades. Associated disorders included chronic gastritis, diabetes mellitus, chronic hepatitis‐C virus infection and chronic kidney disease. The disease showed chronic course with high relapse rate and resistance to various therapeutic modalities including systemic steroid alone and in combination with hydroxychloroquine and cyclosporine. Conclusion We believe that EAE is a peculiar clinical variant in the spectrum of WS, which is characterized by a chronic course, resistance to treatment and high relapse rate. The diagnosis and evaluation of this condition need a close monitoring with repeated clinical, histological and laboratory assessment.